The two deaths of the idea of progress (1800-1968) - Ribes, Alberto Javier (2022)
This article deals with the two deaths of the idea of progress, its ups and downs and developments and the consequences that this process had within solid modernity (1800-1968). The first death of the idea of progress occurred, then, in its own formulation; its program was converted into an extension and deepening of the present. The closure began at the end of the sixties, with a paradoxical turn towards the very abyss of the absolute present and daily life and has culminated in our days. Here is the second death of the idea of progress; murdered, this time, by abandonment.